Meta-Analysis of Determinants of the Incidence of Polycystic Ovarian Syndrome (PCOS) in Indonesia - Nira Khayati; Cusmarih Cusmarih (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
In 2013 the infertility rate in Indonesia has increased to 15-25% of all married couples or 4 to 6 million couples require infertility treatment to get offspring. Infertility in women is generally caused by ovulation disorders, one of the causes of ovulation disorders is Polycystic Ovary Syndrome (PCOS). PCOS is caused by various factors or determinants. The purpose of this study was to analyze the influence of determinants of obesity, stress and employment status factors on the incidence of PCOS in women in Indonesia. This study was conducted with systematic review and meta-analysis. Research data is searched from: PubMed and google scholar. By using the search keywords "determinant AND PCOS", " risk factor AND PCOS", " Factor associated AND PCOS AND adjusted odds ratio", and "Risk Factors AND PCOS AND adjusted odds ratio", "obesity AND PCOS", "stress AND PCOS", "Occupation AND PCOS". Indonesian women who are obese will increase the risk of PCOS incidence by 34 times and statistically significant Odds Ratio (OR 34.32; 95% CI: 10.45 – 112.67; p value < 0.001). Severe stress increases the risk of PCOS by 75 times (OR 75.84; 95% CI: 6.91 – 832.00; p value = 0.0004). and women who have jobs will increase the risk of PCOS events up to 35 times (OR 35.41; 95% CI: 2.81 – 446.69; p value = 0.006). In Indonesian women factors Obesity, stress and employment status can increase the risk of PCOS.